Evaluation of impact of COVID-19 related lockdown on perinatal transmission of HIV infection in Buenos Aires, Argentina (Actualizaciones en Sida e Infectología, 2021)
Background: To evaluate the influence of COVID-19 lockdown in key epidemiological variables regarding prevention of mother-to-child transmission (MTCT) in Buenos Aires city (CABA).   Methods: Retrospective analysis of aggregated MTCT data was gathered from six principal maternity hospitals in Buenos Aires city. Pandemic year (2020) was compared to non-pandemic years 2018-19 individually considering key epidemiological variables. Results: A reduction of total births was observed in 2020 compared to 2019 and 2018 (11640 vs. 14031 and 15978, respectively). Proportion of live births in HIV-infected women (HPW) was 0.88% in 2020 without difference with 2019 and 2018 (0.94% and 0.93%), p>0.05 for all comparisons. Among HPW, intrapartum diagnosis was 2.9% for 2020, with no difference between 2019 (2.25%) and 2018 (9.3%), p>0.05 (all comparisons); 8.8% had antiretroviral therapy (ART) started >28 weeks of gestational age in 2020 vs. 16% and 18.05% in 2018 and 2019 (p>0.05, all comparisons). Prevalence of undetectable viral load at delivery was 67% in 2020 vs 64% in 2018 and 65.4% in 2019 (p>0.05, all comparisons). Perinatal transmission was 0% in 2020 vs 1.33% in 2018 and 2.25% 2019 (p>0.05, all comparisons)   Conclusions: In first wave of COVID 19 pandemic no deleterious impact in the proportion of HPW assisted, HIV intrapartum diagnosis, late ART initiation and MTCT-rate was observed in CABA.
Keywords: HIV; COVID-19; vertical transmission; Latin America